2008
DOI: 10.1159/000172980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary α-Linolenic Acid, Eicosapentaenoic Acid or Docosahexaenoic Acid on Parameters of Glucose Metabolism in Healthy Volunteers

Abstract: Aim: To investigate the effects of α-linolenic acid (ALA) and purified eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA) on fasting concentrations of glucose, insulin, fructosamine, on glycosylated haemoglobin (HbA1c) and on insulin sensitivity. Methods: A randomized strictly controlled dietary study in 48 healthy volunteers (13 males, 35 females) of normal body weight (mean age 25.9 years) with three dietary groups (ALA, EPA and DHA) and a parallel design, consisting of two consecutive periods. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…That FO supplementation only seems to exert an effect on plasma glucose among PPARG2 heterozygotes may explain why previous studies in humans have been unable to show an effect of FO on glucose homeostasis and insulin resistance. We found no effect of FO on glucose homeostasis and HOMA, which is in line with findings by Pedersen et al (2010) in teenage boys and findings from studies in adults (Egert et al 2008;Giacco et al 2007). In contrast, other studies in adults have observed improved insulin sensitivity as a consequence of fish intake or FO supplementation (Abete et al 2008;Ramel et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…That FO supplementation only seems to exert an effect on plasma glucose among PPARG2 heterozygotes may explain why previous studies in humans have been unable to show an effect of FO on glucose homeostasis and insulin resistance. We found no effect of FO on glucose homeostasis and HOMA, which is in line with findings by Pedersen et al (2010) in teenage boys and findings from studies in adults (Egert et al 2008;Giacco et al 2007). In contrast, other studies in adults have observed improved insulin sensitivity as a consequence of fish intake or FO supplementation (Abete et al 2008;Ramel et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Although animal studies are also in line with our finding (Ghafoorunissa et al, 2005;Chicco et al, 2009), some human studies reported either no effect (Finnegan et al, 2003;Egert et al, 2008) or the opposite (Hodge et al, 2007). Some studies have stratified their population by the level of obesity, and reported that total PUFA intake was inversely associated with IR or DM incidence only in subjects with a lower degree of obesity (Colditz et al, 1992;Mayer-Davis et al, 1997;Salmeron et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…The associations of ALA, an inefficient precursor of EPA and DHA in humans (Burdge, 2006), also remain unclear (Barre, 2007). For example, intervention studies failed to find associations between dietary ALA and fasting glucose or insulin concentrations (Finnegan et al, 2003;Egert et al, 2008). While ALA content in adipose tissue or plasma phospholipid was inversely associated with glucose intolerance (Carlson and Walldius, 1975) or DM incidence (Wang et al, 2003), a cohort study found that a high ALA intake was significantly associated with increased DM incidence (Hodge et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Egert et al reported no change in the HbA1c level of individuals who consumed 2.8 g of EPA a day for three weeks. (19) Another study, in which patients consumed 500 mg of EPA a day with or without vitamin C for eight weeks, showed that EPA consumption could reduce HbA1c conspicuously. (20) From these studies, it seems that the duration of intervention plays a key role in the changes in HbA1c levels, since the lifespan of red blood cells is almost 120 days.…”
Section: Discussionmentioning
confidence: 99%